The Ugliness of “Abortion Art” - Tham, L.C., Joseph (Studia Bioethica, 2013)
This article examines the case of the “abortion art” controversy that provoked immediate and universal disgust and condemnation. It analyzes, through the lens of aesthetics and bioethics, some of the reasons for this reaction. First, it looks at the nature of this repulsion toward ugliness, both as an aesthetic experience and as moral intuition and the relation between the two. Then it explores the relation between goodness, truth and beauty in traditional metaphysics and the difficulties posed by modernity. Lastly, it examines the problem of ugliness, which is paradoxically attractive as a false beauty.